2006
DOI: 10.1007/s00464-005-0612-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a training module for the clinical introduction of the da Vinci robotic system in visceral and vascular surgery

Abstract: The presented experimental small and large animal model is a standardized and reproducible training method for robotic surgery that allows evaluation of the surgical performance while shortening and optimizing the learning-curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 36 publications
(54 reference statements)
0
29
0
Order By: Relevance
“…The advantages of robotic techniques over traditional laparoscopy are represented by tridimensional InSite ® view, steady image of the surgical Weld and precise movements, thanks to articulated endoscopic joints yielding seven degrees of freedom, almost like the human hand. The wrested instruments provide for tremor Wltration and scales motion, translating the surgeon's manoeuvres into a Wner dexterity [6,7]. The experience with robotic surgery in gastric cancer is still limited and the oncological outcomes with these techniques are practically unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of robotic techniques over traditional laparoscopy are represented by tridimensional InSite ® view, steady image of the surgical Weld and precise movements, thanks to articulated endoscopic joints yielding seven degrees of freedom, almost like the human hand. The wrested instruments provide for tremor Wltration and scales motion, translating the surgeon's manoeuvres into a Wner dexterity [6,7]. The experience with robotic surgery in gastric cancer is still limited and the oncological outcomes with these techniques are practically unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing number of studies have evaluate the surgeons' performance in either inanimate [6,11,12] or animate [13,14] models by using primarily qualitative measurements. Even though these studies lack direct applicability to clinical settings [13], their convenience and low cost make inanimate models essential during the initial stages of robotic training programs.…”
Section: Introductionmentioning
confidence: 99%
“…Even though these studies lack direct applicability to clinical settings [13], their convenience and low cost make inanimate models essential during the initial stages of robotic training programs. Virtual reality (VR)-a form of inanimate model training-is considered an attractive, inexpensive, and user-friendly mean of motor learning [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have addressed this issue and found that in contrast to open surgery, robotic skills can improve significantly in a relatively short time [56,57]. In robotic-assisted microvascular surgery, it was shown that both fully trained surgeons and residents demonstrate comparable abilities in mastering the procedure, with similar anastomosis times and errors of management (breaking suture, breaking knots, and breaking or damaging needles).…”
Section: Discussionmentioning
confidence: 97%